2018
DOI: 10.1007/s10461-017-2014-0
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Technology for Improving Symptom Management in Low Income Persons Living with HIV

Abstract: Persons living with HIV (PLWH) are living longer but experiencing more adverse symptoms associated with the disease and its treatment. This study aimed to examine the impact of a mHealth application (app) comprised of evidence-based self-care strategies on the symptom experience of PLWH. We conducted a 12-week feasibility study with 80 PLWH who were randomized (1:1) to a mHealth app, mobile Video Information Provider (mVIP), with self-care strategies for improving 13 commonly experienced symptoms in PLWH or to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 35 publications
1
82
0
1
Order By: Relevance
“…Table 3 illustrates a strong preference for the use of surveys (73.0%, 49/67), independently of the timeline, with a prevalence of custom questionnaires (55.0%, 37/67). Almost all studies assessing system usability (which is a frequent interpretation of acceptability, see Table 2 ), made use of standardized surveys, which reflects the range of reliable tools available to evaluate this concept [ 72 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 illustrates a strong preference for the use of surveys (73.0%, 49/67), independently of the timeline, with a prevalence of custom questionnaires (55.0%, 37/67). Almost all studies assessing system usability (which is a frequent interpretation of acceptability, see Table 2 ), made use of standardized surveys, which reflects the range of reliable tools available to evaluate this concept [ 72 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Smartphone use has definite benefits for everyday life. The smartphone technology not only has been adopted by health professionals to facilitate high-quality care (29,30), but also has shown promising results to improve the self-management of chronic conditions (31)(32)(33) including substance use disorders (SUDs) (34,35) through smartphone applications.…”
Section: Discussionmentioning
confidence: 99%
“…diabetes, cardiovascular disease) (6). A recent study testing a symptom self-management mHealth app demonstrated that the intervention group receiving self-care strategies had a significant improvement in symptom burden and medication adherence compared with those in the control group (p=0.017) (7). However, medication adherence was a secondary measure in the study and was limited to a self-report measure (8).…”
Section: Background 11 the Importance Of Medication Adherence In Hivmentioning
confidence: 98%